2019
DOI: 10.1001/jamanetworkopen.2018.7147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Incidence of Hematologic Malignant Neoplasms Among Breast Cancer Survivors in France

Abstract: Key Points Question Which hematologic malignant neoplasm types are more prone to develop after breast cancer diagnosis? Findings In this cohort study of 439 704 French women, breast cancer survivors with an incident breast cancer diagnosis had statistically significantly higher standardized incidence rate ratios of acute myeloid leukemia and myelodysplastic syndrome compared with women in the general population. A slight increase in the incidence of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…In addition, we limited our study to non-dementia patients aged 20 to 85 years because of different treatment approaches in younger and elderly patients and a likely under-reporting of cancer in the geriatric demented population (< 85 years). This cohort has been extensively described in a previous study [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we limited our study to non-dementia patients aged 20 to 85 years because of different treatment approaches in younger and elderly patients and a likely under-reporting of cancer in the geriatric demented population (< 85 years). This cohort has been extensively described in a previous study [13].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study [13], we used the French National Health Data System to estimate the real-life incidence of various hematologic malignancies in BC survivors in the recent era (2007–2015). Herein, we examined the same national cohort to quantify the risk of secondary hematologic malignancies in BC patients according to the specific treatment modalities delivered in the postoperative setting.…”
Section: Introductionmentioning
confidence: 99%
“…The BRCA1 and BRCA2 tumor suppressor genes repair DNA damage to prevent tumor development, and carry a lifetime risk of developing breast cancer and ovarian cancer of up to 84% and 39%, respectively [5] . Regardless of BRCA status, a cohort of over 430,000 women from the French National Health Data System analyzed in 2019 showed that 509 cases of AML developed over a period of 10 years, and AML developed on average 2.4 years after breast cancer diagnosis (95% CI, 1.4–4.0) [6] . These women had treatment including surgical procedures, radiation therapy, chemotherapy, hormonal therapy and growth factors and it was unclear if any specifically had only surgical treatment without other intervention [6] .…”
Section: Case Presentation and Discussionmentioning
confidence: 99%
“…We limited our study to patients aged 20 to 85 years because of different treatment approaches in younger and elderly patients. This cohort has been extensively described in two previous studies 5,11 . Surgical resection being the main treatment for nonmetastatic invasive breast cancer, 12 we restricted the study population to patients who received a surgical intervention as their primary treatment for breast cancer in the 6 months after diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…This cohort has been extensively described in two previous studies. 5,11 Surgical resection being the main treatment for nonmetastatic invasive breast cancer, 12 we restricted the study population to patients who received a surgical intervention as their primary treatment for breast cancer in the 6 months after diagnosis. We further restricted the study to those who started chemotherapy during the 6 months after their surgery for BC.…”
Section: Study Populationmentioning
confidence: 99%